RNAi Silencing of the HaHMG-CoA Reductase Gene Inhibits Oviposition in the Helicoverpa armigera Cotton Bollworm - Wang, Zhijian (Public Library of Science, 2013)
RNA interference (RNAi) has considerable promise for developing novel pest control techniques, especially because of the threat of the development of resistance against current strategies. For this purpose, the key is to select pest control genes with the greatest potential for developing effective pest control treatments. The present study demonstrated that the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase; HMGR) gene is a potential target for insect control using RNAi. HMGR is a key enzyme in the mevalonate pathway in insects. A complete cDNA encoding full length HMGR (encoding an 837-aa protein) was cloned from Helicoverpa armigera (Lepidoptera: Noctuidae). The HaHMGR (H. armigera HMGR) knockdown using systemic RNAi in vivo inhibited the fecundity of the females, effectively inhibited ovipostion, and significantly reduced vitellogenin (Vg) mRNA levels. Moreover, the oviposition rate of the female moths was reduced by 98% by silencing HaHMGR compared to the control groups. One-pair experiments showed that both the proportions of valid mating and fecundity were zero. Furthermore, the HaHMGR-silenced females failed to lay eggs (approximate 99% decrease in oviposition) in the semi-field cage performance. The present study demonstrated the potential implications for developing novel pest management strategies using HaHMGR RNAi in the control of H. armigera and other insect pests.